Lightning Strike- An Environmental Hazard (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
In 29 yrs period from 1980 to 2009 no post- mortem of deceased who died of lightning had been carried out in S.P. Medical College and associate group of Hospitals in Bikaner, Rajasthan. In 2010, 4 cases of lightning were brought dead in mortuary of PBM Hospital Bikaner. We describe the finding of these cases having singeing of hair, superficial burn and arborescent burn. We also discuss the probable causes of occurrence of such cases after lapse of 29yrs.
Keywords: Lightning; Cloud burst; Thunderstorm